HUBUNGAN KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 27 SINGKAWANG - Nadiya Putri, Riski; Dina Anika Marhayani; Kamaruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: (1) determine the level of emotional intelligence of grade 5 students at SD Negeri 27 Singkawang in the IPAS subject; (2) assess the IPAS learning outcomes of these students; and (3) identify whether there is a significant relationship between emotional intelligence and IPAS learning outcomes. This research is a correlational study with a quantitative approach. The instruments used were an emotional intelligence questionnaire and an IPAS achievement test. Data were analyzed using Pearson Product Moment correlation. The findings show that students’ emotional intelligence and IPAS learning outcomes were in the high category. The correlation coefficient was 0.763 with a significance of 0.000 < 0.05, indicating a significant and strong relationship between emotional intelligence and IPAS learning outcomes.